(untitled) (International journal of artificial intelligence, 2025)
Following its independence in 1991, Uzbekistan initiated economic reforms aimed at transitioning to a market economy. However, by 1996, the country shifted towards increased state intervention and an import substitution policy to accelerate industrial development. This approach involved extensive state control over resource allocation, price regulations, and financial policies. High taxes, government expenditures, and restricted access to favorable exchange rates further reinforced state dominance. Additionally, artificial monopolies were created by limiting market entry and granting preferential treatment to select enterprises. Direct government control over businesses and import restrictions through tariff and non-tariff barriers further constrained market competition. This economic model prioritized centralized management and industrial growth but limited private sector development and economic liberalization.